Proposed Cool Coatings with High Near-Infrared Reflectance and Heat Insulation for Asphalt Pavement - Kui Hu; Yujing Chen; Guixiang Chen; Yuzhou Duan; Caihua Yu (Coatings, 2021)
In summer, black asphalt pavement can absorb a considerable amount of solar radiation, which causes its temperature to rise. Heated asphalt pavement can aggravate the urban heat island (UHI) effect and transfer heat downward, which may cause the problem of permafrost thawing beneath pavements. The objective of this study was to develop a novel cool coating layer (CCL) with high near-infrared reflectance and heat insulation to make the surface of asphalt pavement cool. A self-developed test device and method was established to evaluate cooling effects. Based on the experimental results, the optimal coating can cool asphalt pavement by 11.21 °C when the radiation striking the sample surface is 650 W/m2. This coating, called the composite cool coating layer (CCCL), is composed of the following materials: polyurethane resin, rutile TiO2 of 18%, hollow glass microspheres of 12%, and copper chromite black spinel of 0.7%. Silicon carbide particles of 1 kg/m2 can help the CCCL achieve satisfactory antiskid performance. In conclusion, CCCL can effectively inhibit the absorption of solar radiation and reduce the flow of thermal energy downward without sacrificing skid resistance.